Design Water Turbine as Pump Drive for Irrigating Paddy Fields in the Highlands in the Panjalu Ciamis Region - Herdiana, Ade; Riyadi, Slamet (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
In electrical systems, safety is the main factor, but it is often overlooked because it is quite expensive. The current conventional outlet, although it has been standardized by the Indonesian national standard, is a fact in the field that there are still many incidents of electric shock, because the voltage continues to flow through the copper terminals inside the plastic frame protector. This incident can occur because the terminal is plugged into a conducting object such as a fork, spoon, iron rod, or held directly with a finger. For this reason, in this study, a safety system is made that uses the main component of the Relay as an intermediary for DC voltage and AC voltage. Trials carried out 50 times on each socket box resulted in solving the problem by conditioning the plug that had not been plugged into the terminal so that there was no voltage flowing into the outlet, this certainly distinguishes safety from using an ELCB which must have contact with the human body first.